Lyophilized açaí pulp (Euterpe oleracea Mart) attenuates colitis-associated colon carcinogenesis while its main anthocyanin has the potential to affect the motility of colon cancer cells. (November 2018) - Fragoso, Mariana F.; Romualdo, Guilherme R.; Vanderveer, Lisa A.; Franco-Barraza, Janusz; Cukierman, Edna; Clapper, Margie L.; Carvalho, Robson F.; Barbisan, Luis F.
Abstract: This study evaluated the possible protective effects of lyophilized açaí pulp (AP) in a colitis-associated carcinogenesis (CAC) rat model and the modifying effect of cyanidin 3-rutinoside (C3R) on the motility of RKO colon adenocarcinoma cells, using the wound healing assay. Male Wistar rats were induced to develop CAC using 1, 2-dimethylhydrazine (DMH) and 2, 4, 6-trinitrobenzene acid (TNBS). Animals were randomly assigned to different groups that received basal diet or basal diet supplemented with 5.0% or 7.5% lyophilized AP. The findings indicate: 1) C3R (25 μM) has the potential to reduce RKO cell motility in vitro ; 2) ingestion of lyophilized AP reduces the total number of aberrant crypt foci (ACF), ACF multiplicity, tumor cell proliferation and incidence of tumors with high grade dysplasia; 3) AP increases the gene expression of negative regulators of cell proliferation such as Dlc1 and Akt3, as well as inflammation (Ppara). Thus, lyophilized AP could exert a potential antitumor activity. Highlights: AP reduces ACF development and incidence of tumors with high grade dysplasia, and cell proliferation in colon tumors. Cyanidin 3-rutinoside (C3R) has the potential to reduce the motility of RKO cells. AP increases the gene expression of negative regulators of cell proliferation ( Dlc1 and Akt3 ) and inflammation ( Ppara ).